Perbandingan Hasil Face Painting Menggunakan Teknik Manual Dan Teknik Airbrush Pada Makeup Karakter - Divia Indri Paramita; Hayatunnufus Hayatunnufus (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
Prias is not only required to enhance the appearance of the face and hair, but also a total appearance complete with supporting appearance that can reinforce one's character. This study aims to determine the results of face painting using manual techniques and airbrush techniques on character makeup and determine the differences in face painting results between manual techniques and airbrush techniques on character makeup. The type of this research is Quasy Experimental. The study population was 45 students with 4 samples. T test test analysis technique. Based on the research results obtained face painting cosmetology using manual techniques that the highest value is found in the aspects of time efficiency and color sharpness of 3.88 has very good criteria and the lowest on flatness with an average of 2.25 good criteria , the results of face painting make-up using airbrush technique flatness aspect average 3.81 on very good criteria, and at an average time efficiency of 3.88 very good criteria, the lowest on color sharpness with an average of 3.44 good criteria and there are differences in the face painting results between the manual technique and the airbrush technique in the aspect of flatness (p <0.05) and there is no difference in the face painting results between the manual technique and the airbrush technique in the aspect of time efficiency. solid or creamy because the results of cosmetics that are applied can be more flat and directly attached.Keywords: face painting, manual techniques, airbrush techniques, clown character makeup